The grand array writings on nature, science, and spirit - Rogers, Pattiann, 1940- (Trinity University Press, 2010)
"This collection of essays by poet Pattiann Rogers written over twenty-five years, along with three interviews from the same period, lays out Rogers's vision of the essential unity and interdependence of science, spirituality, the arts, and the experience of the physical world"--Provided by publisher.